Genomic single molecule analysis of chromatin structure around DNA replication origins in Saccharomyces cerevisiae - Jeffery, HM (2021)
Origin licensing initiates DNA replication by loading proteins on to DNA. In eukaryotes origin licensing varies among inactive replication origins and can be analysed by looking at chromatin structure. This has predominantly been studied using population-based approaches including MNase-seq. These mask the heterogeneity in interactions between DNA-binding events that occur on the same DNA molecule.